Penerapan Metode Naïve Bayes dalam Peramalan Polusi Udara di Kota Jakarta - Sandy Andika Maulana; Shabrina Husna Batubara; Wahyu Kurnia Rahman (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2023)
This research aims to analyze and predict the level of air pollution in Jakarta City using ISPU data of DKI Province, adopting the Naïve Bayes method. The test results show that the Naïve Bayes algorithm has excellent performance, with 93% accuracy, 98% precision, 100% recall, and 99% f1-score. The implication is that this model can be effectively used for air pollution forecasting in Jakarta City, assisting authorities in making decisions related to air quality and environmental improvement efforts.